An automated system for transactions for the UP Diliman - Main Library Electronic Resources Section - Guillermo, Ryan Gil E. (2010)
Many industries, including libraries, are inclining to automate their services. This is evident in the UP Diliman Main Library. Recent developments have been exporting manual processes into automated applications and database management systems. Accordingly, this applied research is focused on developing an automated system for the Electronic Resources Section of the UP Diliman Main Library.